Massage Therapy on Weight Gain and Motor Development in Children at Risk of Stuntingat Muara Satu Health Center - Erlina, Erlina; Iswani, Rayana; Fatiyani, Fatiyani (Sarana Ilmu Indonesia (salnesia), 2025)
Stunting is a growth and development disorder experienced by toddlers due to prolonged nutritional deficiencies, especially during the first 1,000 days of life. One effective method to address stunting is providing stimulation through infant massage therapy, which functions to promote growth and development. This study aimed to assess the extent to which infant massage therapy affected weight gain and motor development in children under two years old who were at risk of stunting in the working area of Muara Satu Public Health Center, Lhokseumawe City. The study used a quantitative method with a quasi-experimental design and a pretest-posttest control group approach, comparing the conditions before and after the massage therapy intervention. The findings showed that the average difference in infant weight between the intervention group and the control group after the treatment was 0,51 kg. The results of the Independent T-test showed a p-value of 0,196 (p-value >0,05), indicating no statistically significant difference in weight between the two groups after the intervention. Therefore, it was concluded that infant massage therapy did not have a significant effect on increasing the weight of children at risk of stunting. However, in terms of motor development, the Mann-Whitney test showed a p-value of 0,023 (p-value <0,05), indicating a statistically significant difference between the intervention and control groups at post-test. Thus, infant massage therapy was proven to be effective in improving motor development in children under two years at risk of stunting.